A novel active equalizer for Li-ion battery pack in electric vehicles. (February 2019) - Liu, Yu; Xia, Chaoying; Gu, Miao; Xin, Wei; Men, Xuming
Abstract: A novel active equalizer for Li-ion battery pack in electric vehicles is designed. Based on cell-to-pack-to-cell topology, the equalizer consists of a switch array and a single-ended forward bidirectional DC-DC converter, which is simple, efficient and reliable. During discharging process, energy flows from the most charged cell to the battery pack, realizing peak-cut equalization. During charging process, energy transfers from the whole battery pack to the least charged cell, enabling valley-filled equalization. Using synchronous rectification, the equalizer therefore has less conduction loss. Finally, a battery management system (BMS) experimental platform for a 6-series Li-ion battery pack is set up. The experimental results show that it can quickly reduce the difference between maximum and minimum SOC value to less than 5%, which prove the feasibility and effectiveness of the designed equalizer.